Novo regime automotivo brasileiro: desafios e oportunidades da região sul fluminense - Pascoal, Erik Telles [UNESP] (2015)
The public policies of incentives to the national automotive industries have been present since the implementation of this sector in Brazil. As example, in 2012, the federal government created a new Brazilian automotive policy, called Inovar-Auto, from 2013 to 2017, with the purpose of increasing the technological level associated to the products and process of automotive industry and the competitiveness of the sector. The present research aims to analyze and to evaluate the Inovar-Auto development in the automotive center of southern state of Rio de Janeiro, justified in the opportunity of exploit the new encouragement to the R&D and innovation activities for automotive sector, in the growing importance of the study area on the national scene and in a perspective to analysis an industrial public policy program even during its term. A field research was accomplished with companies of the studied region, through an elaborated questionnaire from Inovar-Auto's requirements and applied with directors and managers of these organizations. The results of this research revealed challenges related to the lack of knowledge and the understanding of the program's rules and also, development opportunities from partnerships between suppliers and automakers in R&D and innovations projects. Based on that, it was organized two regional forums of debate, with the purpose to promote a wide explanation of the program, sharing experiences among companies in the southern state of Rio de Janeiro in the conduct of Inovar-Auto's activities and to encourage the partnerships of these companies in R&D and innovation projects